Short Courses of Perfection and Specialization in Lima Callao for Civil Construction Workers - Matos Cubas, Luzmila Olinda (2019)
According to the Ministry of Education, there are several institutions that provide and develop forms of education and training that allow access to technical training for the dispersed population or with difficulty to attend centers that offer specializations at high costs, this is the case of the technical institutions run by the State. As an initial strategy, the realization of a systematization of experiences in technical education in construction in South America, specifically in the courses of improvement and specialization of technicians focused on the construction market, that serve as a framework for future proposals of efficient technical education and effective, assess and recognize the importance of training proposals in technical education and complementary job training.